An examination of language input and vocabulary development of young Latino dual language learners living in poverty. Issue 6 (December 2013) - Boyce, Lisa K.; Gillam, Sandra L.; Innocenti, Mark S.; Cook, Gina A.; Ortiz, Eduardo
The purpose of the study was to evaluate the language status of 120 young, Latino dual language learners living in poverty in the United States. Maternal language input and home language and literacy environments were examined with regard to language development at 24 and 36 months. Results suggested that even when combining English and Spanish language knowledge scores, the children in this sample still performed below, albeit closer to, age level. The home language and literacy environments were significantly related to and predicted child language status at 24 and 36 months. The article discusses the implications of these findings with regard to the focus of early intervention efforts.